2021
DOI: 10.1080/08039488.2021.1946590
|View full text |Cite
|
Sign up to set email alerts
|

Dosing methods in electroconvulsive therapy: should the Scandinavian time-titration method be resumed?

Abstract: Aim: To describe and evaluate the different dosing methods in ECT, and bringing back into focus the Scandinavian time-titration method. Method: A narrative, unsystematic, and selective review and discussion. Results: There are five dosing methods: 1) The Scandinavian time-titration to tonic convulsion, using low-frequency pulses and a long maximal pulse train duration, was highly efficacious with right unilateral (RUL) ECT, comparable to bitemporal (BT) ECT. However, the device used went out of production in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The strength of the electric field induced by conventional ECT is above the excitation threshold of most neuronal tissue in the brain, resulting in activation of almost the entire brain, which may contribute to cognitive SEs 50 . The total charge, pulse width, frequency, train duration and current amplitude all contribute to treatment response, electric field intensity and seizure induction with ECT 51 , 52 . One area of research has focused on modification of stimulus pulse width to enhance efficacy and reduce cognitive SEs of ECT.…”
Section: Optimizing Dosing and Administration Of Ectmentioning
confidence: 99%
“…The strength of the electric field induced by conventional ECT is above the excitation threshold of most neuronal tissue in the brain, resulting in activation of almost the entire brain, which may contribute to cognitive SEs 50 . The total charge, pulse width, frequency, train duration and current amplitude all contribute to treatment response, electric field intensity and seizure induction with ECT 51 , 52 . One area of research has focused on modification of stimulus pulse width to enhance efficacy and reduce cognitive SEs of ECT.…”
Section: Optimizing Dosing and Administration Of Ectmentioning
confidence: 99%
“…The optimal method for individualizing the stimulus dose in ECT is, however, not known. Dose titration at the first treatment, primarily for RUL electrode placement, has been proposed as a feasible option [ 49 , 50 ]. Age-based dosing is standard in Sweden, but the mean total charge found in this study is comparable to or slightly higher than that reported in clinical trials where dose-titration was used [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We may argue that we do not know whether the magnitude of the effect with less invasive load calculation techniques (such as titration or the half-age method). Seizure threshold-based and benchmark dosing seems to be more accurate than fixed high and formulabased dosing [34]. We consider this highly important, as the use of different charge calculation techniques can affect both the duration of the seizure and the effectiveness of ECT [35].…”
Section: Limitationsmentioning
confidence: 99%